2020
DOI: 10.1021/acs.orglett.0c00601
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cluster Activation in a Bacterial Symbiont Leads to Halogenated Angucyclic Maduralactomycins and Spirocyclic Actinospirols

Abstract: Growth from spores activated a biosynthetic gene cluster in Actinomadura sp. RB29, resulting in the identification of two novel groups of halogenated polyketide natural products, named maduralactomycins and actinospirols. The unique tetracyclic and spirocyclic structures were assigned based on a combination of NMR analysis, chemoinformatic calculations, X-ray crystallography, and 13 C labeling studies. On the basis of HRMS 2 data, genome mining, and gene expression studies, we propose an underlying noncanonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[1][2][3] We recently intensified our research efforts on elucidating the defensive functions of Actinobacteria in the fungus-farming termite Macrotermes natalensis [4,5] and found that most of the actinobacterial isolates produced mixtures of secondary metabolites that are active against the co-occurring weed fungi. Within these studies, we became particular intrigued by members of the fairly underexplored genus Actinomadura, [6][7][8] including Actinomadura sp. RB99 as their culture extracts showed antimicrobial activity against bacterial and fungal tests strains.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] We recently intensified our research efforts on elucidating the defensive functions of Actinobacteria in the fungus-farming termite Macrotermes natalensis [4,5] and found that most of the actinobacterial isolates produced mixtures of secondary metabolites that are active against the co-occurring weed fungi. Within these studies, we became particular intrigued by members of the fairly underexplored genus Actinomadura, [6][7][8] including Actinomadura sp. RB99 as their culture extracts showed antimicrobial activity against bacterial and fungal tests strains.…”
Section: Introductionmentioning
confidence: 99%
“…RB99 was grown on 100 ISP-2 agar plates as previously described. , Methanolic culture extracts were subjected to solvent partitioning and analyzed by high-resolution tandem mass spectrometry (HR-MS 2 ). The acquired ESI(−)-MS 2 data were subjected to the Global Natural Product Social Molecular Network (GNPS) platform for MS 2 -based molecular networking analysis, which has already been successfully applied in the identification of novel natural products of diverse origin. Analysis of the resulting MS-based data sets in combination with corresponding UV data resulted in the detection of a unique MS 2 cluster that exhibited characteristic peak patterns of polychlorinated metabolites with characteristic isoflavone-type UV signatures (Figures and S1). Dereplication of the detected HR-MS data was performed using AntiBase and SciFinder and revealed several so far unreported deprotonated molecule ions, each of which correlated to a characteristic m / z halogenation pattern (Figures S3–S8).…”
Section: Resultsmentioning
confidence: 99%
“…While high biomass cultivation induced mostly the formation of rubterolones, growth from diluted spore cultures resulted in the dominant formation of chlorinated maduralactomycin ( 74 ) containing a rare bicyclic 4-chromanone fused with isocoumarin core structure and spirocyclic actinospirols ( 75 ). 124 Intriguingly, the tested cultivation conditions likely simulate the natural ecological environment bacterial strains would face when entering the fungus comb after obligate gut passage of a termite worker. Based on comparative genome studies and HRMS 2 -based GNPS analyses, a putative biosynthetic mechanism was proposed that is based on a non-canonical angucycline biosynthesis and extensive oxidative modifications that ultimately result in the formation of the unique halogenated tetracyclic polyketides and after additional oxidative rearrangements in the formation of actinospirols.…”
Section: Natural Products Reported From the Termite Symbiosismentioning
confidence: 99%
“…Bioactivity studies of maduralactomycin A revealed antibacterial activity towards both Vancomycin-Resistant Enterococcus faecalis and Mycobacterium vaccae. 124 3.3.2 Non-ribosomally synthesized peptides.…”
Section: Reviewmentioning
confidence: 99%